Engaging Future Clinical Oncology Researchers: An Initiative to Integrate Teaching of Biostatistics and Research Methodology into Specialty Training. Issue 5 (May 2016) - Turner, S.; Sundaresan, P.; Mann, K.; Pryor, D.; Gebski, V.; Shaw, T.
Abstract: Aims: To evaluate the learner's perspectives on a novel workshop programme designed to improve skills in biostatistics, research methodology and critical appraisal in oncology. Materials and methods: Trainees were surveyed anonymously at the completion of each annual workshop from 2012 to 2015. In total, 103 trainees in years 2–4 of training in radiation oncology responded, giving a 94% survey response rate. A 1 day workshop, designed by biostatisticians and radiation oncologist facilitators, is the central component of a programme teaching skills in biostatistics, research methods and critical appraisal. This links short didactic lectures about statistical concepts to interactive trainee discussions around discipline-related publications. Results: The workshop was run in conjunction with the major radiation oncology clinical trials group meeting with alternating programmes (A and B). Most of the participants (44–47/47 for A and 48–55/56 for B), reported that their understanding of one or more individual topics improved as a result of teaching. Refinement of the workshop over time led to a more favourable perception of the 'optimal' balance between didactic/interactive teaching: nine of 27 (33%) 'optimal' responses seen in 2013 compared with 23 of 29 (79%) in 2015 ( P  < 0.001). Commonly reported themes were: clinician facilitators and access to biostatisticians helped contextualise learning and small group, structured discussions provided an environment conducive to learning. Conclusions: Overall, radiation oncology trainees reported positive perceptions of the educational value of this programme, with feedback identifying areas where this resource might be improved. This model could readily be adapted to suit other medical disciplines and/or other training environments, using specialty-specific research to illuminate key statistical concepts. Highlights: Attaining skills in research methodology and appraisal of the literature is key to oncology practice. One challenge of clinical/radiation oncology training programmes is engagement of young researchers. Providing context and feedback are key to learning in biostatics and research methodology. Integrated interactive specialty-specific teaching workshops offer a valuable learning opportunity. Access to senior colleague researchers and biostatistician facilitators appears to enhance acquisition of skills.